Synthesis of (2S,3R,5R)-2-Azido-3,5-dihydroxynonadecane Sphingolipid Analogue - Momha, René; Pegnyemb, Dieudonné Emmanuel; Mosset, Paul (Synthesis, 2020)
A concise and highly efficient synthesis of an enigmol analogue has been achieved. The synthetic strategy features Jacobsen’s hydrolytic kinetic resolution (HKR) and epoxide opening by alkynyl boranes as the key steps.
Keywords: sphingolipid; HKR; epoxide; enigmol; β-hydroxyacetylenes